Предмет: Алгебра, автор: andrianabolotvina31

Довести тотожність!!! 20 балів

Приложения:

Ответы

Автор ответа: rahlenko007
0

Ответ:

Объяснение:

\frac{1}{a-b} +\frac{1}{b-c} =\frac{a-c}{(a-b)(b-c)} \\\\\frac{b-c}{(a-b)(b-c)} +\frac{a-b}{(a-b)(b-c)} =\frac{a-c}{(a-b)(b-c)} \\\\\frac{b-c+a-b}{(a-b)(b-c)}=\frac{a-c}{(a-b)(b-c)}\\\\\frac{-c+a}{(a-b)(b-c)}=\frac{a-c}{(a-b)(b-c)}\\\\\frac{a-c}{(a-b)(b-c)}=\frac{a-c}{(a-b)(b-c)}

Похожие вопросы
Предмет: Русский язык, автор: Даша4567435647354375
Предмет: Алгебра, автор: Gopen1